Hanoverian to Windsor Consorts
XXI, 310 p. 11 illus., 8 illus. in color.
Keywords: "This fascinating volume explores how consorts from Caroline of Ansbach to the Duchess of Cambridge negotiated the constraints of their position to create both public and private roles for themselves. Entertaining as well as informative, it illuminates Queen Charlotte’s interest in Kew Gardens, Queen Alexandra’s use of dress as display, and the careful attempts of Prince Albert and the Duke of Edinburgh to make sense of their difficult constitutional position, as well as more controversial figures such as the politically minded Caroline of Ansbach and the scandalous Caroline of Brunswick." –Lisa Hopkins, Sheffield Hallam University, UK This book examines the lives and tenures of the consorts of the Hanoverian, Saxe-Coburg and Gotha, and Windsor monarchs from 1727 to the present. Some of the consorts examined in this volume—such as Queen Elizabeth, the Queen Mother, consort to George VI—are well known while others, including Adelaide of Saxe-Meiningen, consort to William IV, are more obscure. These innovative and authoritative biographies bring a fresh approach to the consorts of this period, revealing their lasting influence on the monarchy. In addition to covering a period that has seen the development of constitutional monarchy and increased media scrutiny of the whole royal family, this volume also looks to the future of the British monarchy, suggesting ways that future consorts can learn from the example of their predecessors. This volume and its companions reveal the changing nature of British consortship from the Norman Conquest to today. Aidan Norrie is Lecturer in History and Programme Leader at the University Campus North Lincolnshire, UK, and the Managing Editor of The London Journal. Carolyn Harris is Instructor in History at the University of Toronto School of Continuing Studies, Canada, and a regular royal commentator in Canadian media. J.L. Laynesmith is Visiting Research Fellow in Medieval Studies at the University of Reading, UK. Danna R. Messer is Senior Acquisitions Editor at Arc Humanities Press, and the Executive Editor of The Encyclopedia of the Global Middle Ages. Elena Woodacre is Reader in Renaissance History at the University of Winchester, UK, Editor-in-Chief of the Royal Studies Journal, and the founder of the Royal Studies Network.